OUR1/OsbZIP1-OsPIN9 regulatory module controls auxin-dependent crown root formation in rice - Dong, Yihao; Wainaina, Cornelius Mbathi; Kojima, Takaaki; Inukai, Yoshiaki (Frontiers in Plant Science, 2025)
Crown root (CR) development is a major determinant of rice root system architecture and influences nutrient uptake, tiller number, and grain yield. Although polar auxin transport mediated by PIN proteins is critical for CR formation, the transcriptional regulation of specific PIN members remains unclear. Here, we demonstrate a novel regulation of OsPIN9 mediated by the bZIP transcription factor OUR1/OsbZIP1. Loss of OUR1/OsbZIP1 function significantly promotes CR formation under nutrient-sufficient conditions, and this induction requires upregulation of the auxin efflux carrier OsPIN9, which we identify as a direct target of OUR1/OsbZIP1. Disruption of OsPIN9 mostly abolished the enhanced CR phenotype of the our1 mutant. Spatially adjacent patterns of upregulated OsPIN9 and enhanced auxin signaling were accompanied by the induction of the CR initiation regulators CRL1, CRL5, and OsWOX11, defining an OUR1/OsbZIP1–OsPIN9 module that integrates auxin transport and signaling to regulate CR development in rice.